FAKTOR YANG MEMPENGARUHI MANAJEMEN LABA PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR DI BEI - Laxamana, Evelyn; Nugroho, Vidyarto (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study aims to obtain evidence about the influence of composition of board commissioners and audit committee as a part of good corporate governance, audit quality, firm size and leverage as independent variables on earnings management as dependent variable of non financial companies listed on Indonesian Stock Exchange from 2018 – 2020. This research used non-financial companies that listed in Indonesia Stock Exchange during 2018-2020 as the population. There are 153 companies, with 459 total data that meet the criteria. This research using purposive sampling method and used multiple regression method to analyze the data. The result shows that composition of board commissioners, audit committee, firm size and leverage have no influence on earnings management while audit quality have influence on earnings management practice.